Aerodynamic characteristics of flapping wings under steady lateral inflow. (15th May 2019) - Han, Jong-Seob; Nguyen, Anh Tuan; Han, Jae-Hung
Abstract : This experimental study investigates the effect of a uniform lateral inflow on the aerodynamic characteristics of flapping wings. Seven designated sideward ratios in the hovering condition and in the presence of a contralateral wing and a body were taken into account as variables in order to secure a better understanding of wing–wing and/or wing–body interactions under the lateral inflow. Our results from the single-wing cases clarified that an inflow running from the wingroot strengthened the leading-edge vortex, thereby augmenting the aerodynamic force/moment. The inflow running in the opposite direction drastically bent the leading-edge vortex to the trailing edge, but the cycle-averaged aerodynamic force/moment was barely changed. This led to substantial imbalances in the force/moment on the two wings. The roll moment on a centre of gravity and the static margin suggested flight instability in the lateral direction, similar to previous studies. We found that the wing–wing interaction was not completely negligible overall under a lateral inflow. A massive downwash induced by the wing on the windward side nearly neutralized the aerodynamic force/moment augmentations on the other wing with lower effective angles of attack. The wing–wing interaction also gave rise to a low-lift high-drag situation during the pitching-up wing rotation, resulting in greater side force derivatives than the theory of flapping counterforce. Further calculations of the roll moment and the static margin with the centre of gravity showed that the wing–wing interaction can improve static stability in the lateral direction. This mainly stemmed from both the attenuation of the lift augmentation and the elimination of the positive roll moment of the flapping-wing system.